PENERAPAN AUDIT OPERASIONAL DALAM MENUNJANG EFISIENSI DAN EFEKTIFITAS PRODUKSI - Hanifati, Fathin; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to comprehend the implementation of operational audit cansupport the efficiency and the effectiveness of production function on PT Candi Jaya Amerta. This research hasbeen carried out by using qualitative descriptive method which is supported by collecting the necessary data,i.e.: documentation and direct interview to the related parties. The comparison between the target and therealization of the production in fulfilling the determined target in producing the order has been obtained fromthe result of the analysis. Based on the result of the analysis of the target and the realization which has beendone in 2013-2014 periods, it has been found that the company is unable to meet the determined target inproducing the order. The different between the production target and the realization of production is the orderwhich has not been realized yet. The order which has not been realized yet is caused by some factors, i.e.: rawmaterials, human resources, and maintenance. It can be concluded from the result of this research that the causeof inefficiency and ineffectiveness on production process, i.e.: delays in raw materials, human resources whichcannot match with the pace of production machines, and can be found by using operational audit, incorrectproduct manufacturing, and maintenance which experiences trouble, so improvement should be carried out andit has made the delays in production process.Keywords: Operational Audit, Effectiveness, Efficiency